Dysphagia as an Unusual Presentation of Myeloma - Raissi, A.; Chahbi, Z.; Zyani, M.; Darouassi, Y. (Case Reports in Hematology, 2018)
Multiple myeloma is a plasma cell dyscrasis characterized by mature B cells proliferation in the bone marrow. In rare cases, the disease can present as an extramedullary location, making diagnosis and management more challenging. Here, we describe a rare case of tongue extramedullary myeloma and discuss diagnostic, prognostic, and therapeutic issues.